Uniportal video-assisted thoracoscopic S8 segmentectomy and S1a subsegmentectomy for synchronous multiple primary lung cancers - Zhang, Guofei; Yu, Zipu; Wang, Lian; Shen, Gang; Chai, Ying (Journal of Thoracic Disease, 2018)
With the increasing incidence of synchronous multiple primary lung cancers (SMPLC), difficulties in diagnosis and decision making for treating patients with SMPLC can result in clinical dilemmas for clinicians. To simplify the diagnostic and treatment course, the less-invasive technique of video-assisted thoracic surgery (VATS) segmentectomy and subsegmentectomy can be selected preferentially. However, segmentectomy and subsegmentectomy are technically more sophisticated compared to lobectomy, and they involve the identification of the nodule locations, confirmation of the targeted structures and ensuring the surgical margin. Here, we describe the performance of uniportal VATS segmentectomy and subsegmentectomy technique in a patient with SMPLC in the right upper lobe with the assistance of three-dimensional (3D) navigation. We detected the intersegmental planes using infrared thoracoscopy with an intravenous injection of indocyanine green (ICG). The patient was discharged with no complication. We think that uniportal VATS segmentectomy is a feasible alternative and technically safe for treating patients with SMPLC.